Detection of Mercury Vapor in Selected Governmental Dental Health Care Centers in Al-Karkh- Baghdad - Saja M. Jebur, Jathwa A. Kareem (Pakistan Journal of Medical & Health Sciences, 2022)
Almost all governmental centers in Iraq are still using mercury amalgam in spite of available alternatives; that make the initial assessment very important to assess the current situation. The survey included visiting (17) site within health centers in three locations in each (the room space, amalgam capsule containers and medical waste storage containers). (510) measurements (10 readings in each location) have been taken for every health care center in Al-Karkh side in Baghdad (10 general health centers, 7 specialists’ center). Potential quantity of emitted mercury vapor has been measured using a portable mercury vapor detection device (TRACKER 3000 IP). Broad variability was noted in the concentration of Hg vapor emitted depending on the amount of empty capsules that were collected, opened or closed container, room area, number of chairs in the room and patients per day, number of full containers and applying environmental and health safety rules. 94.1 % of visited centers exceeded the lowest allowed occupational levels, 76.5 % recorded high concentrations exceeding Ceiling Limit Value while 94.1 % exceeded the Minimum Risk Level. The mercury vapour concentration in work space and the mercury vapour intake by inhalation of chronic daily exposure have linear relation. Mercury dental amalgam and its empty capsules in healthcare centers are a major source of emitting toxic mercury vapor causing chronic and acute exposure to population and for most dentists.